A STUDY OF EMOXIN’S CARDIOPROTECTIVE PROPERTIES IN PATIENTS WITH ACUTE IMPAIRMENT OF CEREBRAL BLOOD FLOW - V. V. Stolyarova (Российский кардиологический журнал)
We have examined fourty-nine patient with an acute disturbance of cerebral circulation (ADCC). Holter ECG monitoring revealed 43% of cases having some episodes of myocardial ischemia. In ADCC the control subjects received complex therapy, the experimental group subjects being given emoxipin in addition. The use of emoxipin was seen to reduce the incidence of myocardial ischemia and to product a positive effect on its structure.